An Unexpected Life Through Comics: An Interview with Ben Katchor - Frederick Luis Aldama (Studies in 20th & 21st Century Literature, 2017)
This interview conducted with Ben Katchor takes readers on a journey through his life, work, and different eras of comic strip and comic book creation. Katchor shares with Frederick Luis Aldama his origins as a word and drawing storyteller as well as his trials, tribulations, and successes throughout the latter 20th century.
Keywords: Comics studies; biography; comic strips; comic practitioner